Self Driving Car - T. , Manikandan; J.S. , Jayashwanth; S. , Harish; K.N. , Harshith Sivatej (International Journal of Psychosocial Rehabilitation, 2020)
A self-driving car is a car capable of sensing its surroundings and moving on its own through traffic and other obstacles with minimum or no human input. This is the current upcoming technology in the automobile industry, and even though it has been discussed and worked on for a long time, it was successfully manufactured by TESLA. In recent years, these cars began to roll out in foreign markets as private and public vehicles (taxis, etc.). Many companies, like Waymo, Uber, Nissan, and Nvidia, are involved in this product development. With this type of car, the whole automotive transportation’s safety, security, and efficiency are increased, and the human errors can be eradicated whilst the drive is made to its best. This project has infused the idea of traffic signal responding, which is absent in the current models, and the above-mentioned advantages can be achieved with much more ease and at a low cost. This type of system can bring a revolution in transportation for differently abled people and also help blind people travel independently.